2021
DOI: 10.1038/s41421-021-00320-y
|View full text |Cite
|
Sign up to set email alerts
|

RBD-homodimer, a COVID-19 subunit vaccine candidate, elicits immunogenicity and protection in rodents and nonhuman primates

Abstract: The pandemic of COVID-19 caused by SARS-CoV-2 has raised a new challenges to the scientific and industrious fields after over 1-year spread across different countries. The ultimate approach to end the pandemic is the timely application of vaccines to achieve herd immunity. Here, a novel SARS-CoV-2 receptor-binding domain (RBD) homodimer was developed as a SARS-CoV-2 vaccine candidate. Formulated with aluminum adjuvant, RBD dimer elicited strong immune response in both rodents and non-human primates, and protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…Taking into account the antigen dose and the number of immunizations achieved, levels of neutralizing antibodies are comparable to other RBD-based vaccines [28]. Based on published data [28,48], an increase in nAbs can be expected with increasing vaccine doses and the number of immunizations.…”
Section: Discussionmentioning
confidence: 68%
“…Taking into account the antigen dose and the number of immunizations achieved, levels of neutralizing antibodies are comparable to other RBD-based vaccines [28]. Based on published data [28,48], an increase in nAbs can be expected with increasing vaccine doses and the number of immunizations.…”
Section: Discussionmentioning
confidence: 68%
“…Different cell types have been used to produce RBD antigens, such as yeast, plant, and insect cells ( 33 , 41 44 ). However, production in mammalian cells ( 12 , 45 49 ) may produce an RBD antigenic domain that more closely resembles that generated during virus infection in human cells (including post-translational modifications such as glycosylation and correct folding) ( 50 ). Our results showing binding to hACE2-expressing cells and the induction of neutralizing antibody titers confirm the preservation of the RBD structure and the suitable exposition of the receptor binding motif (RBM).…”
Section: Discussionmentioning
confidence: 99%
“…While RBD+alum induces significant immune responses, it has been suggested that its immunogenicity should be increased. Different approaches have been proposed to increase its immunogenicity, such as (i) expression as dimer ( 43 , 49 , 65 , 67 ) or trimers ( 45 ), (ii) fusion to carrier proteins like human IgG Fc moiety ( 44 , 67 ), tetanus toxoid ( 12 ), and interferon-α ( 67 ), (iii) addition of pan HLA-DR-binding epitope to enhance helper T cell responses ( 67 ), (iv) using nanoparticles as delivery system ( 42 , 46 , 48 , 53 , 59 ), or (v) addition of immunopotentiators as CpG ( 42 , 43 , 47 , 59 ), MPLA ( 44 ), 3M-052, or a TLR-7/8 agonist ( 45 , 59 ). Here, we demonstrated that the addition of U-Omp19 to RBD + alum formulation was able to increase the induction and breadth of SARS-CoV-2 neutralizing antibody responses, increase the frequency of RBD-specific germinal center B cells, and induce antigen-specific Th1 and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 9, 2021. ; https://doi.org/10.1101/2021.12.07.471590 doi: bioRxiv preprint Different cell types have been used to produce RBD antigens, such as yeast, plant and insect cells 32,[40][41][42][43] . However, production in mammalian cells 11,[44][45][46][47][48] may produce a RBD antigenic domain that more closely resembles that generated during virus infection in human cells (including post-translational modifications such as glycosylation and correct folding) 49 . Our results showing binding to hACE2 expressing cells and the induction of neutralizing antibody titers confirm the preservation of the RBD structure and the suitable exposition of the receptor binding motif (RBM).…”
Section: Discussionmentioning
confidence: 99%
“…While RBD+Alum induces significant immune responses, it has been suggested that its immunogenicity should be increased. Different approaches have been proposed to increase its immunogenicity, such as i) expression as dimer 42,48,65,67 or trimers 44 , ii) fusion to carrier proteins like human IgG Fc moiety 43,67 , tetanus toxoid 11 , interferon-α 67 , iii) addition of pan HLA-DR-binding epitope to enhance helper T cell responses 67 , iv) using nanoparticles as delivery system 41,45,47,52,59 or v) addition of immunopotentiators as CpG 41,42,46,59 , MPLA 43 , 3M-052 or a TLR-7/8 agonist 44,59 .…”
Section: Discussionmentioning
confidence: 99%